Public knowledge, practices, and awareness of antibiotics and antibiotic resistance in Myanmar: The first national mobile phone panel survey - Miyano, Shinsuke; Htoon, Thi Thi; Nozaki, Ikuma; Pe, Eh Htoo; Tin, Htay Htay (PLOS ONE, 2022)
In 2017, the Myanmar National Action Plan for Containment of Antimicrobial Resistance (AMR) (2017–2022) was endorsed by the Ministry of Health and Sports, Myanmar; one of its objectives was to increase public awareness of AMR to accelerate appropriate antibiotic use. This survey aimed to assess the public knowledge, practices and awareness concerning antibiotics and AMR awareness among adults in Myanmar. We conducted a nationwide cross-sectional mobile phone panel survey in January and February 2020. Participants were randomly selected from the mobile phone panel in each of three groups stratified by gender, age group, and residential area urbanity; they were interviewed using a structured questionnaire. Collected data were weighted based on the population of each stratum from the latest national census and analyzed using descriptive and inferential statistics. Two thousand and forty-five adults from 12 regions and states participated in this survey. Overall, 89.5% of participants had heard about antibiotics; however, only 0.9% provided correct answers to all five questions about antibiotics, whereas 9.7% provided all incorrect answers. More than half of participants (58.5%) purchased antibiotics without a prescription, mainly from medical stores or pharmacies (87.9%); this was more frequent in age group (18–29 years) and those in rural areas (p = 0.004 and p < 0.001, respectively). Only 56.3% were aware of antibiotic resistance and received their information from medical professionals (46.3%), family members or friends (38.9%), or the media (26.1%). Less than half (42.4%) knew that antibiotics were used in farm animals. Most did not know that using antibiotics in farm animals could develop resistance (73.2%) and is banned for the purposes of growth stimulation (64.1%). This survey identifies considerable gaps in the knowledge, practices, and awareness about antibiotics among the general population in Myanmar. Continuous public education and awareness campaigns must be urgently conducted to fulfill these gaps, which would aid in promoting antibiotic stewardship, leading to combating AMR in Myanmar.